TAMAN ENERGI TERPADU DALAM MEWUJUDKAN KEMANDIRIAN ENERGI DAN PANGAN DESA - Rivilyo Mangolat Rizky Sitanggang; Yanif Dwi Kuntjoro; Athalia Christina; Annisa Nur Azizah; I Putu Aditya Brama Putra Cakra Negara (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2023)
The development of Renewable Energy Technologies (EBT) has become a new focus in energy technology development. The advancement of EBT technology aligns with the increasing share of renewable energy, which has grown by 2% from 2017 to 2020. From an energy resilience perspective, EBT technology development can also be a solution for the energy crisis in Remote, Rural, and Undeveloped areas (3T). The rural lifestyle dominated by farming and livestock as livelihoods lacks proper waste management. Limited waste management processes, including the burning of crop residues and livestock waste in empty fields, can lead to pollution and diseases. From a Natural Resource perspective, properly processed agricultural and livestock waste, with the support of Human Resources and appropriate infrastructure, can turn into valuable resources for daily life in rural areas. Supporting clean agricultural and livestock waste management, integrated biogas reactors with green spaces such as plantations, hydroponics, and fish ponds can be a solution to achieving clean waste management while simultaneously ensuring food and energy security. Using quantitative methods, including field testing and direct measurement, the input-output percentages of different waste types and the potential of the Integrated Energy Park in supplying energy and food for the village can be calculated.